Design of Condition Based Monitoring on Traction Transformers Using the Fuzzy Mamdani Method - Reimondika, Fegi Arga; Silaban, Freddy Artadima (Journal Sensi: Strategic of Education in Information System, 2024)
Condition Based Monitoring Real-Time, direct supervision of machine condition parameters to detect potential changes, focuses on nitrogen gas pressure and oil temperature of the traction transformer at ASEAN Station, using the Fuzzy Mamdani method. This method notifies the traction transformer's condition and activates fans, providing information to operators. Arduino Uno R3 functions as a receiver and processor of sensor values. These values are processed using Fuzzy Mamdani, sent to ESP8266, and displayed on localhost. Percentage errors for nitrogen gas pressure (3.7%) and temperature (1.55%) result in a total percentage of 5.25%. The Fuzzy Mamdani output is 771.53 with a percentage error of 0.0019%, compared to MATLAB 2023b testing results of 773. Real-time monitoring shows the traction transformer is in good condition, with additional control to maintain its condition and improve reliability.